Studi Hadis Tematik Tentang Self Love - Uswatun Hasanah; Halawatul Kamala; Repa Hudan Lisalam (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
Self love is a very crucial aspect and has a high urgency in our lives. Even the Prophet obliges fellow Muslims to love themselves. This study aims to discuss self love in the perspective of hadith. This study uses a qualitative approach with the application of hadith thematic methods. The main focus of this research is the understanding and application of self love based on hadith themes. The results of this study indicate that hadith themes can be conceptualized in a theoretical framework that describes the importance of self-love in a hadith perspective. In this study it was explained that applying self-love has a very significant role in achieving a happier and healthier life in all its aspects. Self love involves our ability to see ourselves as valuable entities and deserve happiness. The conclusion of this study is by loving ourselves, we will improve the overall quality of life.